PERANAN UREA, Phanerochaete chrysosporium, DAN Trametes sp. TERHADAP KANDUNGAN HEMISELULOSA SERTA SELULOSA PELEPAH DAUN SAWIT SEBAGAI PAKAN HIJAUAN - Ferdian Marga Dinata; Liman .; Farida Fathul (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2012)
The aim of resetcah to determine the role of urea, Phanerochaete chrysosporium, and Trametes sp. the content of hemicellulose and cellulose after fermented. The research was conducted using Completely Randomized Design (CRD) with three replications. Data were analyzed using analysis of variance at 5% level test or 1%, followed by the Least Significant Difference test (LSD). The treatment accorded to the palm leaf midrib P0 = palm leaf sheaths without addition or control; P1 = palm sheaths leaf + urea; P2 =palm sheaths leaf + Phanerochaete chrysosporium inoculum; P3 = palm sheaths leaf +Trametes sp. Inoculums. The results showed that the addition of urea, Phanerochaete chrysosporium, and Trametes sp. fermentation of palm leaf midrib affect the content of hemicellulose and cellulose. Hemicellulose content of the fermentation of palm leaf midrib best found in fermented palm leaf midrib + Trametes sp. and In the parameters contained in cellulose fermentation of palm sheaths leaf without treatment, palm sheaths leaf + urea, palm sheaths leaf + Phanerochaete chrysosporium. Keyword: Palm sheaths leaf, urea, Phanerochaete chrysosporium, dan Trametes sp.